Perawatan Gamelan Pada Laboratorium Seni - Sapto Sapto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
The treatment of Gamelan needs to be handled well. A wrong treatment has a potential threat and shortens the use of an instrument. The purpose of this paper is to identify the treatments of art instrumentation in educational laboratories. The goal is achieved by using the concept of maintenance, namely planned maintenance and unplanned maintenance. Based on that concept, the results show, generally, that gamelan treatment is divided into two parts, namely managerial aspects and practical aspects of instrument maintenance. Maintenance also concerns the problem of storing instruments. It is to anticipate damage as early as possible so as to increase the efficiency and duration of the gamelan. A good Gamelan maintenance prevents damage to the musical instruments that will extend the life of the instrument, and ensure the comfortable and safety use.Keywords: maintenance, gamelan, performance, laboratory, art education